2018
DOI: 10.3390/ma11040537
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inherent Surface and Internal Defects on Mechanical Properties of Additively Manufactured Ti6Al4V Alloy: Comparison between Selective Laser Melting and Electron Beam Melting

Abstract: Additive manufacture (AM) appears to be the most suitable technology to produce sophisticated, high quality, lightweight parts from Ti6Al4V alloy. However, the fatigue life of AM parts is of concern. In our study, we focused on a comparison of two techniques of additive manufacture—selective laser melting (SLM) and electron beam melting (EBM)—in terms of the mechanical properties during both static and dynamic loading. All of the samples were untreated to focus on the influence of surface condition inherent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 51 publications
5
53
0
2
Order By: Relevance
“…Three types of defects were observed, i.e., lack of fusion, shrinkage porosity, and gas porosity, and they are visualized in Figure 3. Such defects have also been previously observed by Goel et al [3], and the influence of the defects on mechanical properties has been elaborated elsewhere [16,17]. Round-shaped gas porosities (refer Figure 3a) were randomly distributed, and they are attributable to entrapped gas inside the virgin powder, which could have found its way into the EBM build [1].…”
Section: Uncoated Conditionsupporting
confidence: 57%
“…Three types of defects were observed, i.e., lack of fusion, shrinkage porosity, and gas porosity, and they are visualized in Figure 3. Such defects have also been previously observed by Goel et al [3], and the influence of the defects on mechanical properties has been elaborated elsewhere [16,17]. Round-shaped gas porosities (refer Figure 3a) were randomly distributed, and they are attributable to entrapped gas inside the virgin powder, which could have found its way into the EBM build [1].…”
Section: Uncoated Conditionsupporting
confidence: 57%
“…In general, this results in higher tensile properties, even if manufactured products are affected by microporosity causing a decrease of elongation respect to wrought products. Nevertheless, the use of various energy sources requires different processing conditions and subsequently produces distinct characteristic features [12]: L-PBF process is performed in an inert gas atmosphere, while EB-PBF in vacuum conditions to avoid the electron beam deflection. During L-PBF, powder particles absorb heat energy from photons, while the electron beam penetrates inside powder converting its kinetic energy into thermal energy.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, SLS can be a good alternative not only for OC tissue engineering, but also for the fabrication of bio-inspired multilayer scaffolds with well-designed architecture and gradient composition. Furthermore, a recent study performed by Fousová et al [22] showed the comparison of other two laser-assisted techniques in the scaffold's production. In this work, the authors compared the architecture and mechanical performance of solid free-form scaffolds composed by a Ti6Al4 V alloy.…”
Section: Stereolithographymentioning
confidence: 99%